Progress of Bamboo Recombination Technology in China - Yuxiang Huang; Yue Qi; Yahui Zhang; Wenji Yu (Advances in Polymer Technology)
At present, China is the world's largest producer of bamboo resource possessor and bamboo processing. The main processing method of bamboo recombination technology is rolling and compaction, by which a reconstituted material with bamboo fibrotic veneer as matrix and phenolic resin as reinforcement is prepared. It has excellent physical and mechanical properties and can replace high-quality wood to manufacture various engineering structural materials and building decoration materials. This paper reviewed the research process and progress of bamboo recombination technology, the existing technical problems and prospects, in order to provide references for future research on bamboo recombination theory and production practice. In recent years, as a new material with controllable properties, designable structures, and adjustable dimensions, bamboo reconstituted materials have been comprehensively studied from the aspects of pressing process parameters, physicochemical mechanical properties evaluation system, and microstructure characterization, but the research is not comprehensive and has not in-depth view. In the future, the relationship between microstructure and performance should be emphatically studied to clarify the law of mechanical performance change and ultimate mechanical performance under synergistic enhancement effect, as well as the performance change and interface formation of the resin during the entire molding process. Meanwhile, the reliability and relevance of applied research should be further expanded, and the integration of natural and artificial aging environment, process and performance, and macro- and microscales should be strengthened.